Work Choices of Married Women: Drivers of Change - Cai, L (My University, 2010)
Developing sound policies to encourage greater female labour force engagement requires a good understanding of the factors affecting the labour supply decisions of women. However, a comprehensive review in 2005 of the literature on the labour supply of Australian women (Birch 2005) pointed out that there remains much to be studied in the field.
Visiting Researcher Papers
Keywords: Gender; Employment -- Labour force participation; Employment; Gender -- Female; Gender; Labour market; Gender; Employment; Female; Labour force participation; Gender; Employment and unemployment